2019
DOI: 10.1007/s10068-019-00584-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutritional characteristics and bioactive compounds of soursop-yoghurt and soursop-frozen dessert

Abstract: The nutritional quality, sensory attributes, polyphenols and acetogenins content in yoghurt and frozen dessert formulated with soursop pulp were investigated. The addition of soursop pulp to yoghurt and frozen dessert improved the sensory attributes and the nutritional quality of soursop dairy products resulting in a composition of 0.92 and 2.17% of dietary fiber, 11.25 and 9.84 mg/100 g of vitamin C as well as 243.02 and 490.98 mg/100 g of total polyphenols, respectively. Acetogenins were extracted from both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…Despite the increasing number of craft breweries and the spread of "fruit beers" as a way to diversify and thus expand the beverage market, there are still few breweries that make technological use of soursop fruit (Annona muricata L.) in the elaboration of craft beers (Bicas et al, 2011;Virgen-Cecena et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increasing number of craft breweries and the spread of "fruit beers" as a way to diversify and thus expand the beverage market, there are still few breweries that make technological use of soursop fruit (Annona muricata L.) in the elaboration of craft beers (Bicas et al, 2011;Virgen-Cecena et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…T.A and pH value are commonly used as quality indicators in dairy products (Virgen-Ceceña et al 2019). Results, also showed that T.A of P.C.A.B treatments were decreased as the rate of P.J.…”
Section: Resultsmentioning
confidence: 76%
“…Consumption of fresh fruit extracts or beverages is growing worldwide, due to the belief that they contribute to a balanced diet and are a good source of antioxidants, vitamins (C, A, B2, and B6) and minerals (potassium, calcium, phosphorus, magnesium, and iron). It also has anti-cancer, anti-inflammatory and anti-tumor capabilities and the potential to minimize the risk of many diseases due to its biological active compounds such as polyphenols and acetogenins (Virgen-Ceceña et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In research conducted by Alves et al (2020), the pH ranged from 3.9 to 4.03 in the three beer formulations created using soursop pulp. The addition of soursop pulp can be a determining factor for the low pH of the beverage after the fermentation process, since the fresh soursop pulp has a pH of between 3.41 and 3.89 (Virgen-Cecena et al, 2019;Velasco-Hernández et al, 2020).…”
Section: Course Of Fermentationmentioning
confidence: 99%